2006
DOI: 10.1269/jrr.47.a171
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Abnormalities in Aspirated Thyroid Cells and Chromosome Aberrations in Lymphocytes of Residents Near the Semipalatinsk Nuclear Test Site

Abstract: Chromosomal studies in peripheral lymphocytes from 63 residents near the Semipalatinsk nuclear test site, at ages of 52-63 years old, were performed in 2001-2002. A higher rate of chromosome aberrations was observed in the two contaminated villages, Dolon and Sarjal, compared with the control village, Kokpekti. Moreover, a relationship of frequency of cells with radiation induced chromosome aberrations and the previously estimated exposure dose was observed. Furthermore, apparent nuclear abnormalities (ANA) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Thyrocytes with giant internuclear bridges may therefore be candidates for the role of specific markers of radiation effects on the thyroid gland, the search for which continues (Tuttle and Becker 2000; Achille et al 2009; Takeichi et al 2006; Zotti-Martelli et al 1999). Further study of the retrospectively detected cellular phenomena in cytological smears obtained after fine needle biopsies of the thyroid gland among people who were exposed in the first months following the Chernobyl accident is of importance to extend understanding of long-term irradiation consequences in the human organism.…”
Section: Resultsmentioning
confidence: 99%
“…Thyrocytes with giant internuclear bridges may therefore be candidates for the role of specific markers of radiation effects on the thyroid gland, the search for which continues (Tuttle and Becker 2000; Achille et al 2009; Takeichi et al 2006; Zotti-Martelli et al 1999). Further study of the retrospectively detected cellular phenomena in cytological smears obtained after fine needle biopsies of the thyroid gland among people who were exposed in the first months following the Chernobyl accident is of importance to extend understanding of long-term irradiation consequences in the human organism.…”
Section: Resultsmentioning
confidence: 99%
“…Since 2018, Kazakhstan has been a member of the ARADOS (Asian Network of Biological Dosimetry) network [ 18 ], which is a platform for radiation dosimetry research among Asian countries. In addition, Kazakhstan has participated in many epidemiological studies using biological dosimetry techniques such as dicentrics, FISH translocations and physical dosimetry methods [ 19 , 20 , 21 , 22 , 23 ] as well as research on the biological effects of radiation on the human body, which further confirms the importance of research in this direction [ 24 ].…”
Section: Introductionmentioning
confidence: 97%
“…In the first four decades of nuclear testing direct individual measurements of the radiation burden to the members of the overexposed population were not carried out either by bioassay or external retrospective dosimetry assays. The studies by biological methods (Ilyinskikh et al 1997 , 1998 ; Tanaka et al 2000 , 2006 ; Testa et al 2001 ; Stephan et al 2001 ; Salomaa et al 2002 ; Chaizhunusova et al 2006 ; Takeichi et al 2006 ) or EPR or TL retrospective dosimetry (Ivannikov et al 2006 ; Stepanenko et al 2006 , 2007 ; Zhumadilov et al 2006 , 2013 ; Sholom et al 2007 ) were not made until the 1990s. Published reports in English language literature are available only after 1995.…”
Section: Scenarios Involving Incorporation Of Radionuclidesmentioning
confidence: 99%
“…Several biological dosimetry studies with the conventional cytogenetic techniques (by unstable chromosome aberrations: DC and MN assays) were performed about five decades after the beginning of the nuclear tests in 1949. These studies suggested that the current increased levels of unstable-type chromosome aberrations in the inhabitants of the most contaminated areas were mainly due to internal exposure (Tanaka et al 2000 , 2006 ; Testa et al 2001 ; Takeichi et al 2006 ) but these methods were not appropriate for long-term individual retrospective dose assessment.…”
Section: Scenarios Involving Incorporation Of Radionuclidesmentioning
confidence: 99%